Efficacy of pre- and post-emergence herbicides in rainy season greengram (Vigna radiata) - KUMAR, NARENDRA; HAZRA, K K; NADARAJAN, N (The Indian Journal of Agricultural Sciences, 2017)
A field study was conducted during kharif season of 2011 and 2012 to assess the efficacy of post-emergence application of Imazethapyr alone or in combination with pre-emergence herbicide Pendimethalin. Treatments comprised four doses of Imazethapyr (40, 60, 80 and 100 g/ha) alone and combination with Pendimethalin @ 1.25 kg/ha and Pendimethalin @ 1.25 kg/ha + manual weeding. The study reveals that the yield loss due to weed competition in kharif season greengram [Vigna radiata (L.) Wilczek] was to the tune of 62%. Weed control efficiency was highest in Pendimethalin @ 1.25 kg/ha + Imazethapyr @ 100 g/ha as pre- and post-emergence combination. Similar trend was also observed in plant biomass, nodulation and yield attributes. Grain yield (839 kg/ha), net return (Rupees 16 060/ha) and B: C ratio (1.77) were also highest in Pendimethalin @ 1.25 kg/ha + Imazethapyr @ 100 g/ha. Thus, pre-emergence application of Pendimethalin @ 1.25 kg/ha followed by post-emergence application of Imazethapyr @ 100 g/ha at 25 days after sowing may be recommended for effective weed management in kharif season greengram.